الأسماء المنصوبة في سورة مريم (دراسة تحليلية على نظرية تمام حسان) - Fajri, Ahmad Maulana; Kasim, Amrah; Haniah, Haniah; Hijab, Zainal Abidin (Diwan : Jurnal Bahasa dan Sastra Arab, 2024)
تهدف هذه الدراسة إلى تحليل الظاهرة اللغوية الأسماء المنصوبة في سورة مريم، مع التركيز على الأنماط النحوية والدلالية، وكذلك تأثيرها على فهم النص القرآني. استخدمت الدراسة منهجًا وصفيًا تحليليًا مع اعتماد نظرية تمام حسن كإطار تحليلي. تم جمع البيانات الرئيسية من سورة مريم (98 آية)، بالإضافة إلى البيانات الداعمة المتمثلة في كتب التفسير والدراسات اللغوية ذات الصلة. أظهرت النتائج أن شكل المفعول به هو الأكثر هيمنة وذلك في 71 آية، مع وظائف متنوعة مثل التأكيد وتعزيز المعنى. وخلصت الدراسة إلى أن البنية النحوية في سورة مريم لا تثري فقط الأبعاد الدلالية، بل تحمل أيضًا دلالات مهمة في تعليم اللغة العربية المستندة إلى القرآن الكريم. تُساهم هذه الدراسة بشكل كبير في تطوير أساليب تدريس اللغة العربية والتفسير المعاصر. Abstract This study aims to analyze the linguistic phenomenon of Al-asmā’ al-manṣūbah (nouns in the accusative case) in Surah Maryam, focusing on grammatical and semantic patterns and their implications for Qur'anic interpretation. A descriptive-analytical approach was employed, using Tammam Hassan’s linguistic theory as an analytical framework. Primary data were drawn from Surah Maryam (98 verses), supported by references to tafsir and relevant linguistic studies. The results reveal the prevalence of maf’ūl bih forms in 71 verses, serving various functions such as emphasis and meaning enhancement. This study concludes that the grammatical structures in Surah Maryam not only enrich the semantic dimensions but also have significant implications for Arabic language education based on Qur'anic texts. The study contributes to advancing contemporary linguistic and exegetical methodologies.